Electrochemical synthesis of α-thiocyanato-α-carbonyl sulfoxonium ylides. (26th October 2022) - Zhang, Li-Ming; Yuan, Da-Fu; Fu, Zi-Hao; Li, Hao-Ran; Li, Ming; Wen, Li-Rong; Zhang, Lin-Bao
Graphical abstract: Abstract: An electrochemical protocol for the synthesis of α-thiocyanato-α-carbonyl sulfoxonium ylides via CH thiocyanation by reacting sulfoxonium ylides with potassium thiocyanate was established under simple and mild conditions (room temperature, under air and an undivided cell). Moreover, the method without the requirement of catalysts, additives, oxidants or supporting electrolytes, provides a green pathway of functionalization of sulfoxonium ylides.